Metagenomic assembled dataset of potentially polyethylene terephthalate-degrading microcosms enriched from seawater, cow dung, and landfill soilNCBI SRA - Aubrey Dickon Chigwada; Henry Joseph Oduor Ogola; Memory Tekere (Data in Brief)
We present a dataset of 99 prokaryotic metagenome-assembled genomes (MAGs) derived from 180-day culture-enrichment microcosms of seawater, landfill soil, and cow dung, with polyethylene terephthalate (PET) as the sole carbon source. The recovered MAGs met the medium-to-high quality standards of the Minimum Information for Metagenome-Assembled Genomes (MIMAG) criteria with completeness ranging from 76.5% to 100% and low contamination levels (<10%). The majority of the MAGs were obtained from seawater (52), followed by cow dung (28), and landfill soil (19). Additionally, the dataset includes detailed DRAM (Distilled and Refined Annotation of Metabolism) functional profiles of the MAGs, which highlight the potential role of these microorganisms in the biodegradation of PET polymers. This genomic data provides valuable reference information on bacteria and archaea with the potential capacity to biodegrade plastic, contributing to our understanding of microbial plastic biodegradation.